LIFE AND WORK OF THE UZBEK POET MUHAMMAD YUSUF - Hasanova Barchinoy Kimsanovna, Isroilova Odinaxon G'anijonovna (American Journals, 2023)
This article provides information about the work of the famous poet of the Uzbek people, Muhammad Yusuf, and the stages of the creation of his poems.
Keywords: poet, works, uzbek library, love, uzbek people, heart, lyrics.